2016
DOI: 10.3233/jad-160619
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Cognitive Enhancement Therapy for Patients with Mild Cognitive Impairment and Mild Dementia: A Multi- Center, Randomized, Controlled, Double-Blind, Crossover Trial

Abstract: We developed and evaluated the effect of Multimodal Cognitive Enhancement Therapy (MCET) consisting of cognitive training, cognitive stimulations, reality orientation, physical therapy, reminiscence therapy, and music therapy in combination in older people with mild cognitive impairment (MCI) or mild dementia. This study was a multi-center, double-blind, randomized, placebo-controlled, two-period cross-over study (two 8-week treatment phases separated by a 4-week wash-out period). Sixty-four participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 31 publications
3
76
0
2
Order By: Relevance
“…Next, some studies showed a positive effect on depression scores among patients who received intervention [60], but some studies also showed no effects [70]. The studies that assessed quality of life of the patient and the caregiver found that quality did not improve more than in control conditions in most studies, except for Han et al [70] that found a positive effect on the quality of life of the patient (but not the caregiver). Finally, considering the quality of the studies examining mixed interventions, we found no important differences between the different studies.…”
Section: Mixed Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, some studies showed a positive effect on depression scores among patients who received intervention [60], but some studies also showed no effects [70]. The studies that assessed quality of life of the patient and the caregiver found that quality did not improve more than in control conditions in most studies, except for Han et al [70] that found a positive effect on the quality of life of the patient (but not the caregiver). Finally, considering the quality of the studies examining mixed interventions, we found no important differences between the different studies.…”
Section: Mixed Trialsmentioning
confidence: 99%
“…Some studies included elderly at risk for dementia [67], elderly with mild cognitive impairments [63,70], patients with mild to moderate dementia [64,66], moderate to severe dementia [69], diagnosed with Alzheimer disease [61,62,64,65,68], or a combination of these patients [59,60]. Assessment of cognitive impairment was mostly conducted with the MMSE, but also with other measurements (ADAS-Cog, Clinical Dementia Ranking -CDR).…”
Section: Mixed Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further five were non-randomised (QA 100%) and seven were quantitative descriptive (QA 100%) (see Quality Appraisal in Online Appendix 3). Han et al (2017) was the only double-blind or cross-over trial. Three were conducted across multiple centres: Graessel et al (2011) and Oswald, Gunzelmann, and Ackermann (2007) in German nursing homes, and Serda`i Ferrer and del Valle (2014) in Spanish day hospitals.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…For example, Graessel et al (2011) had the most sessions (288), Oswald et al (2007) had the most weeks (52) and Ibarria et al (2016) had the greatest total time commitment of 979 hours (approximated, see Table 3). Because of the nature of a cross-over trial, the length of wash-out period and the relatively short 32 Dementia 0(0) intervention time of eight weeks in Han et al (2017) they acknowledged that these may have limited the effect of the Multimodal Cognitive Enhancement Therapy (MCET). Since they achieved a small ES for the dementia subgroup, perhaps the overall ES was only hindered by the study duration, and that a longer study might have been more efficacious.…”
mentioning
confidence: 99%